Demographic trends in marital status / divorce rates across generations - Dumitrescu, Nicu (Université d'Ottawa | University of Ottawa, 2020)
In this paper, I used survey and census data to estimate Canadian divorce trends and patterns, since recent vital statistics are not available. I also studied the factors that influence divorce rates across generations. My research seeks to provide a better understanding of changes in patterns of family formation and dissolution, specifically on divorce trends in Canada. I investigated several demographic and socioeconomic factors related to divorce such as marital history, economic resources, and demographic characteristics. The demographic characteristic of age allows determining which generation drives the current trends in divorce rates. I compared my findings with other demographic studies about divorce trends in Canada.